Pubic Candida Folliculitis: A Case Report in a Patient With Recurrent Vaginal Candidiasis - Ikemefuna Okwuwa; Nimat Alam; Rachel Wai; Miriam Shayeb; Asley Sanchez; Kushal Gandhi; John Garza; Gary Ventolini (Tehran University of Medical Sciences, 2023)
Objective: Folliculitis is a skin infection and inflammation that develops in the hair follicles. While most cases of folliculitis are caused by bacterial infections, here is a case of folliculitis caused by the Candida fungi in an immunocompetent host. Case report: A 23-year-old non-diabetic immunocompetent female with recurrent vaginal candidiasis developed clusters of erythematous, pruritic papules in the pubic area. Upon evaluation, the clusters were determined to be folliculitis. Risk factors for folliculitis included shaving of the pubic area, hot tub use, and wearing of tight, restrictive clothing. Cultures and skin samples of the folliculitis demonstrated Candida albicans. The patient was subsequently and successfully treated with clotrimazole solution and cream. There was no recurrence of the folliculitis upon her 3-month follow-up appointment. Conclusion: Candida folliculitis is a rare condition in non-diabetic patients. The patient's history, risk factors and immune status assessment, and physical examination with proper diagnostic testing, are crucial steps in attaining the correct diagnosis.